Review of genus Nicephora Bolívar (Orthoptera, Tettigoniidae, Meconematinae) - Wang, Hanqiang; Li, Miaomiao; Liu, Xianwei; Li, Kai (Zootaxa, 2013)
This article presents a revision on all species of genus Nicephora Bolívar, 1900, describes 1 new species distribute in China ally to this genus. A key to species of the genus is given.